Diagnostic Competence of Pre-service Mathematics Teachers: Unpacking a Complex Construct - Tyagi, Tarun Kumar (Voices of Teachers and Teacher Educators, 2023)
Despite efforts for equity and access to mathematics education for all, the number of struggling students is trapped in a vicious circle of unsatisfactory performance to achieve the learning outcomes in mathematics. Nevertheless, against the backdrop of the large-scale heterogeneity of students in Indian classrooms, the diagnostic competence of mathematics teachers plays a significant role in students' mathematics learning. Ergo, the present study aimed to examine the level of diagnostic competence of pre-service mathematics teachers. Descriptive survey method was used to conduct the study. Forty-two final year pre-service mathematics teachers participated in the study. A self-developed tool based on the Perception- Interpretation- Decision-Making (P-I-D) triad model (Blomeke et al., 2015) was administered to the selected sample. Non-parametric statistics x² test was used to analyse the data. The findings reveal a low level of diagnostic competence of pre-service mathematics teachers along with dimensions (detecting, describing, and remediating). Further, according to the findings, very few pre-service mathematics teachers have L-5 diagnostic competence i.e., providing remediation specifically after describing the error pattern in students' response accurately and exploring the possible reasons. Furthermore, gender difference was not found in the diagnostic competence of pre-service mathematics teachers. The findings of the study highlight the pressing need to develop a support system for enhancing the diagnostic competence of pre-service mathematics teachers to ensure early diagnosis and remedial support for the struggling students. Implications and directions for further research are outlined.